Trajectories of health system use and survival for community-dwelling persons with dementia: a cohort study - Bronskill, Susan E (BMJ Open, 2020)
OBJECTIVES: To determine the long-term trajectories of health system use by persons with dementia as they remain in the community over time. DESIGN: Population-based cohort study using health administrative data. SETTING: Ontario, Canada from 1 April 2007 to 31 March 2014. PARTICIPANTS: 62 622 community-dwelling adults aged 65+ years with prevalent dementia on 1 April 2007 matched 1:1 to persons without dementia based on age, sex and comorbidity. MAIN OUTCOME MEASURES: Rates of health service use, long-term care placement and mortality over time. RESULTS: After 7 years, 49.0% of persons with dementia had spent time in long-term care (6.8% without) and 64.5% had died (30.0% without). Persons with dementia were more likely than those without to use home care (rate ratio (RR) 3.02, 95% CI 2.93 to 3.11) and experience hospitalisations with a discharge delay (RR 2.36, 95% CI 2.30 to 2.42). As they remained in the community, persons with dementia used home care at a growing rate (10.7%, 95% CI 10.0 to 11.3 increase per year vs 6.7%, 95% CI 4.3 to 9.0 per year among those without), but rates of acute care hospitalisation remained constant (0.6%, 95% CI −0.6 to 1.9 increase per year). CONCLUSIONS: While persons with dementia used more health services than those without dementia over time, the rate of change in use differed by service type. These results, particularly enumerating the increased intensity of home care service use, add value to capacity planning initiatives where limited budgets require balancing services.